(untitled) (Research, Society and Development, 2022)
Objective: To analyze the temporal trend of hospitalization for femur fracture in Brazil and regions from 2001 to 2020. Methodology: This is an ecological, descriptive and exploratory study on femur fractures in Brazil and regions. The information was collected from the Hospital Information System (SIH/SUS) of the Information Technology Department of the Unified Health System (DATASUS). Central tendency and rate-type measures were calculated, the latter being the Standardized Hospital Admission Rate (SPT). The temporal trend was estimated by the JoinPoint model. Results: In Brazil, over the 14 years analyzed, 1,175,403 hospitalizations for femoral fractures were recorded. The average of IPTp in Brazil was 43.19 hospitalizations for every 100 thousand inhabitants (SD=2.44). The time trend of TPIH in Brazil was of growth with a VPA of 1.2% per year. The North showed a growth trend with 1.3% per year, the Northeast also presented growth of 2.4%, as well as the South with 1.3% and the Midwest with 0.6%. Conclusion: Brazil had high rates of hospitalization for femoral fractures. The temporal trend was of growth in all regions and in the country.